(untitled) (Third Sector Social Economic Review, 2023)
“Diplomacy”, defined as the art of interstate negotiation, is a term used in international relations. It is shaped according to the effective communication skills of diplomats on various issues. An important type of diplomacy of the last period is a new form of diplomacy known as digital diplomacy. Digital diplomacy is defined as the use of the internet and modern communication technologies to achieve diplomatic goals. Thus, without changing the rules of diplomacy, on the contrary, it is possible to raise it to the level of wider gains. In this context, the main purpose of the article is to explore the importance of soft power in digital diplomacy. It is to determine that soft power plays an important role in public diplomacy and it is possible to use it effectively to achieve a diplomatic goal through digital diplomacy in the 21st century. As a method, the historical origin and development of diplomacy has been researched from the relevant scientific sources. The article covers the examination of digital diplomacy, the modern form of diplomacy, with examples in social media as well as scientific works. Soft power, after all, is a power that does not define the ability of a country or organization to influence others and achieve their goals through attraction and persuasion rather than coercion. Soft power is the ability to shape the preferences and behavior of others through culture, values, and other non-coercive ways. It is based on building relationships, encouraging cooperation, and winning hearts and minds. Therefore, it is seen as a more effective and sustainable way in the modern world.